Noni (Morinda Citrifolia) Ethanol Extract Lowered Blood Glucose Levels, Increased Glutathione Peroxidase Activity, And Decreased Malondialdehyde in White Rats Model of Diabetes - I Putu Dedy Arjita; I Putu Bayu Agus Saputra; Dhika Juliana Sukmana (Postgraduate, University of Mataram, 2023)
Diabetes mellitus can increase oxidative stress and damage cells. Noni fruit has antibacterial, antifungal, antitumor, analgesic, hypotensive, and anti-inflammatory benefits, can boost immunity, and has antioxidant content. Noni contains phenolic compounds (anthraquinones, acuities, asperulosides, and scopoletin), organic acids (capric and caprylic acids), and alkaloids (xeronine). The effect of noni ethanol extract can significantly reduce blood glucose (P<0.05) of the T2 group (177.00±137.78) and T3 (159.40±86.53) when compared to the C+ group (511.00±131.45). The T1 group (387.40±170.06) had no significant difference (P>0.05) when compared to the C+ group (511.00±131.45), but there was a decrease in the average yield at T1 (387.40±170.06). Serum malondialdehyde (MDA) examination showed a significant decrease (p<0.05) in T1 (1188.32±93.41), while in T2 (1385.35±38.65) and T3 (1460.32±42.51) was not significant (p<0.05). Examination of serum glutathione peroxidase (GPX) showed a significant decrease in T1 (119.97±37.45), there was a decrease in GPX levels, while in the T2 group (236.14±6.05) and T3 (185.24±43.07), there was no decrease. Noni ethanol extract can lower blood glucose levels, reduce Malondialdehyde levels, and prevent increased activity of the enzyme glutathione peroxidase. Flavonoid compounds in noni ethanol extract can avoid increased blood glucose and reduce free radicals formed due to hyperglycemia conditions.